Allometric-kinetic model predictions of radionuclide dynamics across turtle taxa. (June 2023) - Whicker, Jeffrey J.; Gerard, Jamie L.; Inglis, Jeremy D.; Conrad, Cyler
Abstract: Chelonians (turtles, tortoises, and sea turtles; hereafter, turtles) inhabit a wide variety of ecosystems that are currently, or have the potential in the future to become, radioactively contaminated. Because they are long-lived, turtles may uniquely accumulate significant amounts of the radionuclides, especially those with long half-lives and are less environmentally mobile. Further, turtle shells are covered by scutes made of keratin. For many turtle taxa, each year, keratin grows sequentially creating annual growth rings or layers. Theoretically, analysis of these scute layers for radionuclides could provide a history of the radioactivity levels in the environment, yet there are few previously published studies focused on the dynamics of radionuclide intake in turtles. Using established biochemical and ecological principles, we developed an allometric-kinetic model to establish relationships between the radionuclide concentrations in turtles and the environment they inhabit. Specifically, we calculated Concentration Ratios ( CRs – ratio of radionuclide concentration in the turtle divided by the concentration in the soil, sediment, or water) for long-lived radionuclides of uranium and plutonium for freshwater turtles, tortoises, and sea turtles. These CRs allowed prediction of environmental concentrations based on measured concentrations within turtles or vice-versa. We validated model-calculated CR values through comparison with published CR values for representative organisms, and the uncertainty in each of the model parameters was propagated through the CR calculation using Monte Carlo techniques. Results show an accuracy within a factor of three for most CR comparisons though the difference for plutonium was larger with a CR ratio of about 200 times for sea turtles, driven largely by the uncertainty of the solubility of plutonium in sea water. Highlights: Long-lived turtles could accumulate significant amounts of environmental radionuclides. We developed an allometric-kinetic model predicting radionuclide dynamics among turtles. Model Concentration Ratios were compared to ratios for similar species and existing data. Comparisons show general accuracy of the model and elucidate research needs.